Digitalization of Teacher Personality Competency Development - Nurul Annisa Zulmi; Daeng Ayub Natuna (CV Bumi Spasial, 2025)
To adapt to their students' demands, instructors must always be up-to-date, master technology and information advancements, and be proficient with technology. In addition to technological gadgets and other teaching aspects that contribute to achieving educational objectives, the teacher's personality is a crucial factor in the success of education. Because interpersonal contact may foster connection and warmth between instructors and students, technological advances do not inherently render this interaction obsolete or even obsolete. Whether or whether communication is effective is generally decided by both parties; yet, because teacher learning is paramount, effective communication mostly depends on the instructor's personality. When utilizing technology, instructors must use network apps for communication. Network apps maintained by educators should be stocked with student-friendly and valuable content. For example, they create online character-building groups with students based on widely accepted norms.